HAK PEKERJA PASCA PERUSAHAAN DIAKUISISI - CHRISTINA NM TOBING (JURNAL ILMIAH KOHESI, 2023)
The purpose of this research is to find out the rights of workers due to the company being acquired by another company according to the Labor Law before and after the Job Creation Law. This research is normative legal research, the data sources used are secondary data in the form of legislation, expert opinions, and research results. The research approach used is the statutory approach. Data analysis was carried out qualitatively. The results of the research, before and after the Job Creation Law, workers' rights in the event that a company is acquired by another company according to the Labor Law, in principle, has given equal rights to employers, where each party can choose not to continue the employment relationship (PHK) or vice versa, continue the employment relationship. Nonetheless, the decision to lay off or no longer be given to employers is implied in the words of Article 163 paragraphs (1) and (2) of the Manpower Law jo. Article 42 paragraph (1) PP No. 35 of 2021 with the words "employers can" carry out layoffs. If the worker wants the employment relationship to end and the employer does not lay off the employee, it can be interpreted that the worker has resigned, so that the worker only gets compensation money according to Article 156 paragraph (4) of the Manpower Law. The Job Creation Law through Article 42 paragraph (2) PP No. 35 of 2021 has added conditions for workers who are not willing to continue working after the company's acquisition, namely changes to working conditions, so that in addition to that workers are required to continue working relations, except for employers who acquire who are not willing to accept workers. Workers' rights to severance pay are smaller after the enactment of the Job Creation Law. This shows that the protection of workers' rights due to layoffs after the Job Creation Law has decreased compared to what was regulated in the previous labor law.